Some conditions of holomorphism in the Hilbert spaces - Bondar , A. V.; Romanenko , V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
New conditions for the C-differentiability of R-differentiable mappings are obtained and a theorem on the holomorphicity of the mappings that have finite dilatation along cones is proved.